Study of the formation of amorphous carbon and rGO-like phases from palmyra sugar by variation of calcination temperature - Fahmi Astuti; Novita Sari; Vera Laviara Maghfirohtuzzoimah; Retno Asih; Malik Anjelh Baqiya; Darminto Darminto (Jurnal Fisika dan Aplikasinya, 2020)
We have processed biomass from palmyra sugar to produce allotrope carbon by heating process with the variation of calcination temperature. The formation of amorphous carbon (a-C) was confirmed from the XRD result heated at 400°C with the observation of the peak at the position of ~24o. By increasing the temperature at 700°C, the presence of two peaks at 24o and 43o were observed, indicating the formation of rGO-like phase. The functional groups detected by FTIR spectra consist of C=C, C-O, C=O, C-H and O-H. The result of conductivity measurement exhibits that the material can be classified as semiconducting materials.